Analisis Faktor-Faktor Penyebab Kecelakaan Akibat Kerja Pada Pekerja Konstruksi: Literature Review - Nunik Sulistyaningtyas (Unit Publikasi Ilmiah Perkumpulan Intelektual Madani Indonesia, 2021)
The number of work accidents in Indonesia is still quite high where every year the number has increased. This increase in the number of work accident cases, especially in the construction sector. A work accident can occur if there are various contributing factors simultaneously in a workplace or production process. The purpose of this literature review is to analyze the factors that cause work-related accidents in construction worker. The method used in this research is a library study approach. The data obtained from the journals that have been collected by the authors are then analyzed carefully. The results of the analysis of these journals show that the human factor dominates as a factor causing work accidents, then environmental factors and equipment factors. The conclusion of this study is that in general the factors that cause work accidents in construction workers are caused by human factors (Unsafe Actions).